Anion receptor-mediated multicomponent synergistic self-assembly of porphyrin for efficient phototherapy to elicit tumor immunotherapy. (October 2022) - Wang, Kui; Chen, Jie; Lin, Lin; Yan, Nan; Yang, Weihu; Cai, Kaiyong; Tian, Huayu; Chen, Xuesi
Abstract: Immunogenic phototherapy has the potential to enhance tumor immunotherapy. Nevertheless, its efficacy is severely restricted by optimal photosensitizer deficiency and efficient delivery of the photosensitizers. We thus constructed TAPP-GCP@TCPP@BSA nanoparticles by self-assembling of a porphyrin derivative (TAPP-GCP), meso-tetra(4-carboxyphenyl) porphyrin (TCPP), and bovine serum albumin (BSA) to achieve effective phototherapy and further enhance tumor immunotherapy. Nanoparticles (NPs) subjected to laser irradiation can induce tumor cytotoxicity and immunogenic cell death (ICD). They can accumulate in tumors after intravenous injection and induce significant ICD after laser illumination, thereby promoting the maturation of antigen-presenting cells and activating the specific antitumor killing effect of cytotoxic T cells in a breast tumor model. NPs combined with anti-PD-L1 blockade significantly inhibited distant tumor growth by initiating an excellent antitumor immune response. The phototherapy of NPs through multicomponent synergistic self-assembly is a promising approach for boosting immune checkpoint blockade therapy. Graphical Abstract: Self-assembled novel nanostructured photosensitizers (TAPP-GCP@TCPP@BSA) can generate singlet oxygen and possess a good photothermal ability. Moreover, the nanophotosensitizers can elicit efficient tumor immunogenic cell death, which can remodel the tumor immunosuppressive microenvironment, and allows for integration with checkpoint blockade therapy for the inhibition of distant tumor. ga1 Highlights: Nanophosensitizers was constructed by weak interaction, and phototherapy for tumor was achieved. The nanodrug exhibited multi-mode imaging, and induced immunogenetic cell death (ICD) for tumor cells. ICD strategy decreased the immune suppression and reversed the suppressive tumor microenvironment. The photo-immunotherapy strategy accomplished an efficient inhibition of distant tumor.